International volunteerism and development in Asia‐Pacific - Yea, Sallie; Sin, Harng Luh; Griffiths, Mark (The Geographical journal, 2018)
In Asia, and across the “global South”, volunteerism has grown enormously in the last two decades. Hundreds of thousands of people now undertake work on development projects in poorer areas of the global South, and volunteerism has become a key way in which cross‐cultural encounters form relations of development between poor and rich countries and between marginal and empowered subjects. Reflecting this growth, geographical discussions of volunteerism have expanded over the past decade. While initial work lauded the benefits and positive potentials of international volunteerism, more recent work and popular media have increasingly questioned such views and suggested that, instead, international volunteerism has the propensity to replicate colonial relationships, and benefits are heavily skewed towards volunteers. These criticisms themselves bear witness to deeper structural and ideological concerns principally centred around the pervasive neoliberalisation of international volunteering and volunteer tourism. Yet, despite its critics, international volunteering remains one of the most common and easily accessible ways in which (any)one can “care for” or “do their part” to address social and economic injustices in the global South. This themed section extends critical discussions of volunteerism in Asia‐Pacific by questioning its developmental effects – including effects that are material, relational and discursive. Through the six papers in this themed section, and insights gained from fieldwork in Singapore, Japan, Cambodia and India, we consider the impacts of international volunteerism; the infrastructure and organisations promoting volunteerism; the subjective positionalities of volunteers; and how marginal populations experience volunteerism.